Does Migration Lead to Income Diversification in Rural Areas? A case Study in Cilacap Regency, Indonesia - Rubiyanto, Cahyo Wisnu; Widadie, Fanny; Seleky, Rosalia Natalia; Alamsyah, Ikhsan Fajar (P4W IPB, 2025)
Migration plays a crucial role in the income augmentation efforts of numerous Asian nations, although its effect on income diversification is still uncertain. This study observed 168 households with 78 migrant households in four villages in Binangun and Nusawungu districts of Cilacap Regency, Indonesia to support their livelihoods and how remittance and income is distributed among them. The data was analyzed by Binary Logistic Regression analysis a statistical technique utilized for modeling the association between a dependent variable and independent variables, family size, land area, livestock count, remittances, total income, total investment, and migrant status. The results demonstrate substantial differences in income between households with migrants and those without migrants, highlighting the vital impact of remittances and the importance of small and medium-sized enterprises (SMEs) on developing rural economies. The results of statistics showed that remittances and total income had p-values of 0.000, highlighting their crucial role in the process of diversifying livelihoods. The limited impact of livestock suggests that it serves as a supplementary asset, whereas the lack of relevance of family size, land area, and investment implies that these factors may not be the main factors driving diversity in the research area. These findings enhance the overall comprehension of rural livelihoods by illustrating the diverse functions that various forms of capital have in determining household strategy. Additional study is required to enhance our comprehension of the interaction among remittances, migration, and livelihood strategies, establishing a basis for data-driven policies that promote economic resilience and expansion in rural regions.